A new species of Balaustium von Heyden, 1826 (Acari: Actinotrichida, Erythraeidae) from Spain - Mąkol, Joanna; Arijs, Yves; Wäckers, Felix (Zootaxa, 2012)
An erythraeid mite, Balaustium hernandezi sp. nov., was found in large numbers in a greenhouse in Spain. The larva,deutonymph and female of the new species are described based on material obtained during experimental rearing. Dataand information on feeding habits, food spectrum, mode of reproduction and life cycle are provided. The potential role of the species as a biological control agent is discussed.